Efficacy of stem cell therapy for diabetic kidney disease: a systematic review and meta-analysis - Du, Hongyu; Xie, Chen; Yuan, Yiqin; Luo, Yun; Cao, Jinguo; Li, Zhihai; Yuan, Jiayi; Li, Wei (Frontiers in Medicine, 2025)
Background/objectivesAnimal studies have demonstrated the ability of stem cell therapy (SCT) to treat diabetic kidney disease (DKD). However, the efficacy of SCT in patients with DKD remain unclear. This systematic review and meta-analysis aimed to investigate the efficacy of SCT in patients with DKD.MethodsA comprehensive and systematic literature search was conducted using PubMed, EMBASE, Cochrane Library, and Web of Science to identify articles on SCT for DKD published up to March 2024. RevMan V.5.4 software was used for statistical analysis.ResultsWe identified four studies that included 90 participants, 53 (58%) of whom underwent SCT. SCT improved estimated glomerular filtration rate (eGFR) [mean difference (MD) = 0.41, 95% confidence interval (CI): 0.08–0.74; p = 0.02], serum creatinine (SCr) reduction (standardized MD = −0.65, 95% CI: −1.19 to −0.1, p = 0.02), and microalbuminuria (MAU) (MD = −32.10, 95% CI: −55.26–8.94; p = 0.007) compared to the control group, but did not improve urine microalbumin/creatinine ratio (UACR) (MD = −63.36, 95% CI: −194.52–67.79, p = 0.56) or blood sugar (MD = 0.49, 95% CI: 4.16–2.01, p = 0.49). Adverse events (AEs) were common (67 events in 60 SCT subjects vs. 35 in 28 controls), with urinary system AEs occurring exclusively in the SCT group and nervous system AEs markedly higher.ConclusionSCT can effectively improve eGFR and SCr levels by lowering the MAU but cannot improve UACR and blood sugar levels.